Negotiating business transactions an extended simulation course - Bradlow, Daniel D. (New York Wolters Kluwer Law & Business, 2013)
The only offering of its kind, Negotiating Business Transactions: An Extended Simulation Course contains facts and contextual materials, negotiating instructions for each side, and background readings on all aspects of the transaction. The text is an introduction to both negotiations and transactional legal practice, and meets the ABA practical skills requirements. By bringing a business deal into the classroom, the text helps students study objectives, structures, and strategies and learn by doing in a setting where mistakes become lessons--not malpractice. The text enables students to develop negotiating and drafting skills as they experience the "real time" challenges of negotiating deals. Students explore the interaction between business and legal issues in the context of structuring those deals. Then, they can apply what they have learned to produce a solution that meets the client's objectives and is acceptable to the counterparty. Finally, by understanding the social and environmental impacts of business transactions, students can more fully explore issues of professional responsibility in negotiations
Includes bibliographical references and index.
Keywords: Commercial law -United States